Applying Lean Manufacturing tools to minimize waste in a mass consumption food company - Lagos, Maricielo (2022)
The Bakery and Confectionery industry has expanded over the years and the products that make it up have taken an established place in people's diets. Many companies today seek to increase their market share while adding value to their products using fewer resources through process optimization, waste elimination, increased performance and productivity. Because of that the purpose of this research work is to provide the concepts of the Lean Manufacturing methodology and its Kaizen, Total Productive Maintenance (TPM) and Centerline tools, an example of its application in mass food consumption companies. Likewise, the application of the Lean methodology and its tools is carried out to a case study developed in a transnational cookie company with the purpose of guaranteeing the achievement of the internal objectives of the company, evaluating the processes and identifying the waste that is generated. in the production process to propose possible solutions.